Avaliação do passivo ambiental de solos degradados por sais no perímetro irrigado Curu Pentecoste, Ceará - Albuquerque, José Alfredo de (2015)
The research has as a physical basis the Curu Pentecoste Irrigated Perimeter, under jurisdiction of the Departamento Nacional de Obras Contra as Secas (National Department of Works to Combat Drought) and as an objective quantify the extent, the cost of reversal and legal responsibility for the environmental liability. The public irrigation in the Brazilian semi-arid has generated salt-induced soil degradation as a by-product, originating a legal liability, and its legal responsibility lies with the state authority. To quantify the extent and cost of reverting the environmental damage, initially, a survey was conducted among irrigating farmers to analyze the meaning they give to the problems related to the irrigation, the water used in irrigation and the degradation of the soil. Beforehand an electromagnetic induction sensor was used to measure the electrical conductivity in the soil, estimating the total of soluble salts in its solution. The electrical conductivity values obtained by the sensor oriented the collection of soil samples for the purposes of physical and chemical analyses, proceeding to the identification of the areas degraded by salt. With the definition of the extent of the environmental damage, the values of the main crops and the gross value of the agricultural production were collected to assess the costs of reverting the environmental liability. The results showed financial and technical insufficiencies of the irrigating farmers; that the environmental degradation by salt reaches 67,27% of the irrigated perimeter. In conclusion, as a result of the solidarity aspects, the strict civil liability in repairing the environmental damage caused by irrigation lies with the state authority.